Synthesis of a New DPTYEAP Ligand and Its Complexes with Their Assessments on Physical Properties, Antioxidant, and Biological Potential to Treat Breast Cancer - Abbas Fadhil Yasir; Hayder Obaid Jamel (Indonesian Journal of Chemistry, 2023)
A new series of complexes of the 2-((1E,2E)-1,2-diphenyl-2-(thiazol-2-ylimino)ethylidene)amino)phenol (DPTYEAP) has been synthesized by the reaction of the ligand with metal chlorides of Ni(II), Cu(II), Pt(IV), and AgNO3 in ethanol as a solvent. The ligand was prepared for the two steps. In the first step, compound (A) was synthesized by reacting 2-aminothiazol with benzil in ethanol. Another step is the preparation of the ligand from the reaction of compound (A) with 2-aminophenol. The structures of the ligand and its complexes were confirmed by FTIR, 1H-13C-NMR, UV-Vis spectra, melting points, molar conductivity (C, H, and N), and magnetic susceptibility. The synthesized complexes were prepared in a 1:2 ratio for Ni(II), Cu(II), and Pt(IV) complexes and a 1:1 ratio (M:L) for Ag(I) complexes. The geometric shape of all complexes is octahedral, except for the Ag(I) complex, which is tetrahedral. The antioxidant test for the prepared compounds was carried out. The anticancer test was conducted for each of the ligands and the platinum(IV) complex, and it was found that the platinum complex is more effective against breast cancer cells (MCF-7); thus, it can be used as a potential drug after studying it well.